Coronary bypass surgery versus stenting in multivessel disease involving the proximal left anterior descending coronary artery. Issue 6 (20th September 2016) - Cavalcante, Rafael; Sotomi, Yohei; Zeng, Yaping; Lee, Cheol Whan; Ahn, Jung-Min; Collet, Carlos; Tenekecioglu, Erhan; Suwannasom, Pannipa; Onuma, Yoshinobu; Park, Seung-Jung; Serruys, Patrick W
Abstract : Objective: In patients with multivessel disease and proximal left anterior descending artery (LAD) involvement, the best revascularisation strategy is still unclear. We assess outcomes after coronary artery bypass graft surgery (CABG) and percutaneous coronary intervention (PCI) with drug-eluting stents in a pooled analysis of individual patient-level data of the SYNTAX and BEST randomised trials. Design: Proximal LAD involvement was defined by any lesion ≥ 50% diameter stenosis in the arterial segment starting from the left-main bifurcation up to (and including) the origin of the first major septal branch. The primary endpoint was the composite of all-cause death, myocardial infarction (MI) or stroke at 5 years of follow-up. Results: The present study population comprises 1166 patients of which 577 were randomised to PCI and 589 to CABG. Baseline characteristics were well balanced across study arms. The primary endpoint occurred in 94 (16.3%) patients in the PCI arm and in 68 (11.5%) patients in the CABG arm (HR 1.43; 95%CI 1.05 to 1.95; p=0.026). CABG was also associated with a significantly lower rate of cardiac death (p=0.007), MI (p<0.001), all-cause revascularisation (p<0.001) and major adverse cardiovascular and cerebrovascular events (all-cause death, MI, stroke, revascularisation) (p<0.001). The rates of all-cause mortality (p=0.06) and stroke (p=0.09) were not statistically different between the two groups. The overall study results for the primary outcome were consistent across several subgroups. Conclusions: In patients with multivessel disease with proximal LAD involvement, CABG is associated with lower rates of the safety composite endpoint of death, MI or stroke as compared with PCI with drug-eluting stents at 5 years of follow-up (number needed to treat=21). Trial registration number: PRECOMBAT clinicaltrials.gov NCT00997828 ; SYNTAX: clinicaltrials.gov identifier: NCT00114972 NCT00114972.